2013
DOI: 10.1002/dev.21183
|View full text |Cite
|
Sign up to set email alerts
|

I spy with my little eye: Typical, daily exposure to faces documented from a first‐person infant perspective

Abstract: Exposure to faces is known to shape and change the face processing system; however, no study has yet documented infants' natural daily first‐hand exposure to faces. One‐ and three‐month‐old infants' visual experience was recorded through head‐mounted cameras. The video recordings were coded for faces to determine: (1) How often are infants exposed to faces? (2) To what type of faces are they exposed? and (3) Do frequently encountered face types reflect infants' typical pattern of perceptual narrowing? As hypot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
221
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 202 publications
(233 citation statements)
references
References 54 publications
11
221
1
Order By: Relevance
“…Facial input received during the first 3 months is sufficient to drive a visual preference for own-race faces in infants (Bar-Haim, Ziv, Lamy, & Hodes, 2006;Kelly et al, 2007). Such preference coincides with 1-to 3-month-olds' natural daily exposure to faces documented from their own first-person perspective (Sugden, Mohamed-Ali, & Moulson, 2014). Infants at that age are exposed predominantly to own-race faces, particularly to female and adult faces of their own race.…”
Section: How Are Infants' Visual Experiences Linked To Processing Faces?supporting
confidence: 68%
“…Facial input received during the first 3 months is sufficient to drive a visual preference for own-race faces in infants (Bar-Haim, Ziv, Lamy, & Hodes, 2006;Kelly et al, 2007). Such preference coincides with 1-to 3-month-olds' natural daily exposure to faces documented from their own first-person perspective (Sugden, Mohamed-Ali, & Moulson, 2014). Infants at that age are exposed predominantly to own-race faces, particularly to female and adult faces of their own race.…”
Section: How Are Infants' Visual Experiences Linked To Processing Faces?supporting
confidence: 68%
“…Sugden, Mohamed-Ali, and Moulson (2014) examined daily exposure to faces of 1-and 3-month old infants through head-mounted cameras. Although face size is not among the variables reported in this article (Sugden et al, 2014), it was nevertheless coded. The authors found that faces smaller than 58 comprised only 12% of total duration of face exposure-88% percent of duration occurred with larger faces (personal communication).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, socio-ecologically-relevant stimuli are typically the most common environmental stimuli [28]; therefore, an action-perception mechanism may develop through experiential canalization, a developmental process that ensures the reliable emergence of important features of the organism, across diverse environments [29]. That is, the early postnatal period may be a sensitive period during which the social environment alters the neural organization of action observation and production.…”
mentioning
confidence: 99%